2014
DOI: 10.1111/febs.13140
|View full text |Cite
|
Sign up to set email alerts
|

Structural basis of multivalent galactose‐based dendrimer recognition by human galectin‐7

Abstract: Galectins are evolutionarily conserved and ubiquitously present animal lectins with a high affinity for b-galactose-containing oligosaccharides. To date, 15 mammalian galectins have been identified. Their involvement in cell-cell and cell-matrix interactions has highlighted their importance in signal transduction and other intracellular processes. Human galectin-7 (hGal-7) is a 15 kDa proto type galectin that forms a dimer in solution and its involvement in the stimulation and development of tumour growth has … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 82 publications
(115 reference statements)
0
13
0
Order By: Relevance
“…The X-ray structure of galectin-7 in complex with synthetic galactose-based dendron with three arms (galectin-7/D2 (4UW5)) was reported (13). In this structure, each galactose-terminus of the three arms of D2 is recognized by one galectin-7 molecule (Fig.…”
Section: N-glycan-type Branched Oligossacharides (17)mentioning
confidence: 99%
See 1 more Smart Citation
“…The X-ray structure of galectin-7 in complex with synthetic galactose-based dendron with three arms (galectin-7/D2 (4UW5)) was reported (13). In this structure, each galactose-terminus of the three arms of D2 is recognized by one galectin-7 molecule (Fig.…”
Section: N-glycan-type Branched Oligossacharides (17)mentioning
confidence: 99%
“…As Arg239 and Glu258 In galectin-9_N-CRD/LN3 (2ZHM) (16), the bound LN3 has a linear structure which enables GlcNAc −1 to form a hydrogen bond with Asn48. Furthermore, Ala46, which is unique to galectin-9_N-CRD, is proposed to be one of the residues responsible for the high affinity for oligolactosamines (13). This is because an amino acid residue with bulky side chain group at the position of Ala46 (His223 in galectin-9_C-CRD and/or Gln47 in galectin-8_ N-CRD) causes steric hindrance with GlcNAc −1 of LN3.…”
Section: +1mentioning
confidence: 99%
“…48 The secondary structure is similar to prototype galectins such as galectin 7 and galectin 10 or Charcot-Leyden crystal protein. 49,50 The C-terminal CRD is of chimera-type galectin (galectin 3). 51 The typical structural alignment of these proteins showed five-stranded (F1-F5) and six-stranded (S1-S6 a/ S6b) b-sheets stabilized by one or two alpha-helices at their ends ( Figure 3).…”
Section: Physical and Chemical Characteristics Of Pp13mentioning
confidence: 99%
“…Experiments done with placental PP13/galectin 13 showed that it contains phosphorylation sites. Computational analysis indicated sites for serine/tyrosine kinase phosphorylation at positioning Ser48 (44)(45)(46)(47)(48)(49)(50)(51)(52)(53)(54)(55)(56)(57) and Tyr41 (37)(38)(39)(40)(41)(42)(43)(44)(45) and Tyr80 (76)(77)(78)(79)(80)(81)(82)(83)(84) close to CRD domain. The carbohydrate binding affinity was observed to be the same in PP13-B (placentally expressed phosphorylated) and PP13-R (bacterially expressed non-phosphorylated).…”
Section: Placental Implantationmentioning
confidence: 99%
“…The substitution at position 74 of an arginine by a serine inhibits the carbohydrates-binding activity of galectin-7 but does not alter the capacity of galectin-7 to form homodimers in solution [ 42 ]. This indicates that binding to oligosaccharides is not required for galectin-7 to form homodimers even if it can slightly modify its conformation and influence the dimers’ stability [ 43 , 44 ]. Regarding carbohydrate binding, galectin-7 displays preferential binding to internal or terminal LacNAc repeat carried by N -glycan ( Figure 1 a) [ 21 , 22 ].…”
Section: Introductionmentioning
confidence: 99%